Mutagenesis of the NaChBac sodium channel discloses a functional role for a conserved S6 asparagine - O’Reilly, Andrias O. (Eur Biophys J, 2017)
Asparagine is conserved in the S6 transmembrane segments of all voltage-gated sodium, calcium, and TRP channels identified to date. A broad spectrum of channelopathies including cardiac arrhythmias, epilepsy, muscle diseases, and pain disorders is associated with its mutation. To investigate its effects on sodium channel functional properties, we mutated the simple prokaryotic sodium channel NaChBac. Electrophysiological characterization of the N225D mutant reveals that this conservative substitution shifts the voltage-dependence of inactivation by 25 mV to more hyperpolarized potentials. The mutant also displays greater thermostability, as determined by synchrotron radiation circular dichroism spectroscopy studies of purified channels. Based on our analyses of high-resolution structures of NaChBac homologues, we suggest that the side-chain amine group of asparagine 225 forms one or more hydrogen bonds with different channel elements and that these interactions are important for normal channel function. The N225D mutation eliminates these hydrogen bonds and the structural consequences involve an enhanced channel inactivation.